1994
DOI: 10.1016/s0969-2126(00)00020-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a soluble, glycosylated form of the human complement regulatory protein CD59

Abstract: The main features of the protein structure are two antiparallel beta-sheets (a central one with three strands and another with two), a short helix that packs against the three-stranded beta-sheet, and a carboxy-terminal region that, although lacking regular secondary structure, is well defined and packs against the three-stranded beta-sheet, on the opposite face to the helix. We have used the structure, in combination with existing biochemical data, to identify residues that may be involved in C8 binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 55 publications
(63 reference statements)
5
142
0
2
Order By: Relevance
“…After incubation of native, undenatured CD59 with PNGase F, the protein migrated as a narrow band with an apparent molecular mass of approximately 15 kDa. This indicated that the glycoform population had been digested by the enzyme and that the Asn 18 -sugar amide linkage is fully accessible to PNGase F. These data are consistent with NMR analyses of glycosylated forms of CD59, which provided little evidence for protein-sugar interactions beyond the first N-acetylglucosamine residue of the N-linked glycan (17,18). Moreover, incorporation of model oligosaccharides in structure calculations (18) suggested that the N-glycan projects away from the protein in the plane of the disc-like extracellular domain.…”
Section: Molecular Modeling Studies Of Cd59 (Fig 1h)supporting
confidence: 64%
See 2 more Smart Citations
“…After incubation of native, undenatured CD59 with PNGase F, the protein migrated as a narrow band with an apparent molecular mass of approximately 15 kDa. This indicated that the glycoform population had been digested by the enzyme and that the Asn 18 -sugar amide linkage is fully accessible to PNGase F. These data are consistent with NMR analyses of glycosylated forms of CD59, which provided little evidence for protein-sugar interactions beyond the first N-acetylglucosamine residue of the N-linked glycan (17,18). Moreover, incorporation of model oligosaccharides in structure calculations (18) suggested that the N-glycan projects away from the protein in the plane of the disc-like extracellular domain.…”
Section: Molecular Modeling Studies Of Cd59 (Fig 1h)supporting
confidence: 64%
“…The full signif- icance of glycosylation for the structure and function of CD59 can only be explored properly when its glycan population is viewed in the context of the complete structure of the molecule. In previous work, the three-dimensional structure of the protein component of CD59 (17,18) and the location of the active site of the molecule 2 have been determined. The aim of the present study was to determine the structure of both the GPI anchor and the N-and O-linked glycans of CD59 in order to complete the initial structural analysis and to provide a context for considering the function of the glycosylation of the molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each domain (D1, D2 and D3) is related to a family of single-repeat, GPI-anchored surface proteins that include CD59, the Ly-6 antigens as well as snake neurotoxins [15,16]. The disulfide bond pattern of D1 conforms to the general structure of the Ly-6/neurotoxins protein family and has suggested overall structural homology to CD59 and snake a-bungarotoxin for which a tertiary structural analysis is available [17][18][19]. The purified amino terminal domain (D1) of uPAR possesses independent ligand-binding activity, although with an affinity 1,500 fold lower than the wild type [1]; the purified carboxy-terminal fragment (D2D3) appears to be devoid of binding activity [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…The precursor of human CD59 is a single peptide composed of 128 amino acids deduced from its cDNA sequence (6,7). The mature protein consists of 77 amino acids arranging in a single cysteine-rich domain composed of two antiparallel β-sheets, 5 protruding surface loops and a short helix (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%